Bird predation does not explain spatial variation in insect herbivory in a forest-tundra ecotone - Zverev Vitali; Zvereva Elena L; Kozlov Mikhail V (SPRINGER, 2022)
The contribution of bird predation to the spatial variations in insect herbivory remains imperfectly understood, especially in Arctic ecosystems. We experimentally tested the hypothesis that the differences in insect herbivory between tundra and forest biomes, and between plant life-forms in these biomes, are associated with differences in the intensity of bird predation on defoliating insects. We observed substantial variation in herbivory (0% to 20% of foliage lost) among nine forest, mountain tundra, and lowland tundra sites in the Kola Peninsula (northwestern Russia) and among five woody plant species, but we found no consistent differences in herbivory between biomes and between plant life-forms. Bird attacks on artificial caterpillars were tenfold more frequent in forest than in tundra, while bird exclusion effects on herbivory did not differ between biomes, and the intensities of bird predation measured by these two methods were not correlated. Bird exclusion led to increases in insect herbivory, and this effect was significant in trees and tall shrubs but was not significant in dwarf shrubs in either forest or tundra sites. Bird predation, as measured in bird exclusion experiments, increased with an increase in the level of foliar damage inflicted by insects in forests but not in tundra habitats. We conclude that bird predation generally decreases plant losses to insects in both forest and tundra habitats, but birds are unlikely to shape the spatial patterns of plant losses to insects in Arctic ecosystems.